Marshmallow sun roast & O Canada (Canadian Medical Education Journal, 2018)
Marshmallow sun roastLocation: Grouse Mountain, BCHypothermia, trauma, concussion and death. All these are acceptable risks many of us are willing to take to enjoy our favorite winter outdoor activities. Medicine is not just about keeping people in perfect health, but to enable us to do what we love. After all, “life is not measured by the number of breaths we take, but by the moments that take our breath away”._____O CanadaIt’s a lot easier to sit back and relax when it’s the only logical option available. Some say laughter is the best medicine, and I believe it’s best delivered in nature with good company.